Educational Management Following the Early Childhood Educational Standards under the Buriram Primary Educational Service Area Office 1: Educational Management Following the Early Childhood Educational Standards under the Buriram Primary Educational Service Area Office 1 - Thongwijit, Kanjana; Vajarintarangoon, Kovit; Wongtongcharoen, Bunphot (RATANABUTH JOURNAL, 2025)
The objectives of the research were 1) to examine the current conditions and desirable conditions and needs following the early childhood educational standards, and 2) to study guidelines for developing educational management following the early childhood educational standards by mixed methods research for the educational institution of Buriram Primary Education Service Area Office 1. The research was divided into two phases. Phase I was to study the current and desirable conditions and needs following the multi stage - sampling. The sample group was 320 teachers. The study used a structured questionnaire to collect data. The data analytics were used including percentage, mean, standard deviation, and needs index to analyze the results. Phase II involved establishing guidelines for educational management following the early childhood education standards through interviewing five experts selected by purposive sampling. The results of the research were as follows: 1) The overall current conditions were at a high level. The aspect with the highest average was child-centered approach. For the overall desirable conditions, the aspect with the highest average was administration and management processes. The need for educational management following the early childhood educational standards development can be prioritized as children’s quality, administration and management processes, and child-centered approach, respectively. 2) The guidelines to develop were as follows: For children’s quality, school administrators should promote integrated learning by developing mathematical and scientific skills. Administration and management processes, school administrators should continuously promote internal evaluation and quality assurance. And child-centered approach, school administrators should encourage parental involvement in evaluating the quality of student learning.